Aedes aegypti Aag-2 Cell Proteome Modulation in Response to Chikungunya Virus Infection - Vasconcellos, Anna Fernanda; Melo, Reynaldo Magalhães; Mandacaru, Samuel Coelho; de Oliveira, Lucas Silva; de Oliveira, Athos Silva; Moraes, Emily Caroline dos Santos; Trugilho, Monique Ramos de Oliveira; Ricart, Carlos André Ornelas; Báo, Sônia Nair; Resende, Renato Oliveira; Charneau, Sébastien (Frontiers in Cellular and Infection Microbiology, 2022)
Chikungunya virus (CHIKV) is a single-stranded positive RNA virus that belongs to the genus Alphavirus and is transmitted to humans by infected Aedes aegypti and Aedes albopictus bites. In humans, CHIKV usually causes painful symptoms during acute and chronic stages of infection. Conversely, virus–vector interaction does not disturb the mosquito’s fitness, allowing a persistent infection. Herein, we studied CHIKV infection of Ae. aegypti Aag-2 cells (multiplicity of infection (MOI) of 0.1) for 48 h through label-free quantitative proteomic analysis and transmission electron microscopy (TEM). TEM images showed a high load of intracellular viral cargo at 48 h postinfection (hpi), as well as an unusual elongated mitochondria morphology that might indicate a mitochondrial imbalance. Proteome analysis revealed 196 regulated protein groups upon infection, which are related to protein synthesis, energy metabolism, signaling pathways, and apoptosis. These Aag-2 proteins regulated during CHIKV infection might have roles in antiviral and/or proviral mechanisms and the balance between viral propagation and the survival of host cells, possibly leading to the persistent infection.